Understanding racial-ethnic differences in patient-centered care (PCC) in oncology through a critical race theory lens: A qualitative comparison of PCC among Black, Hispanic, and White cancer patients. Issue 7 (July 2022) - Mitchell, Kerri-Anne R.; Brassil, Kelly J.; Osborne, Margaret L.; Lu, Qian; Brown, Richard F.
Abstract: Objectives: Patient-centered care (PCC) experiences can vary by race and ethnicity and likely contribute to cancer care disparities. We compared PCC concepts between Non-Hispanic White (White), Hispanic, and Non-Hispanic Black (Black) cancer patients utilizing Critical Race Theory (CRT) to understand the relationships between racial-ethnic identity and PCC. Methods: A thematic analysis and in-depth CRT-informed analysis of individual interviews exploring patient values, unmet needs, preferences, and priorities were performed. Results: Participants were aged> 25 yrs old, 53% male, and included 5 Hispanic, 4 Black and 6 White cancer patients. Unmet needs for time to make decisions, and provider interaction between visits and the value for finding meaning in the illness emerged among Blacks and Whites. The unmet need for a long-term treatment plan emerged among Blacks, and the preference of research participation among Whites. A value for optimism was observed among Hispanics and Whites. Racial-ethnic variations in patient descriptions and experiences of their values, unmet needs, preferences, and priorities were identified. Conclusions: Underrepresented groups face subtle but significant challenges in feeling cared for and understood, voicing concerns, and obtaining quality care. Practice Implications: Increased mutual understanding and provider knowledge of unique PCC experiences among underrepresented cancer patients are needed. Highlights: Patient-centered care (PCC) concepts vary by race and ethnicity in oncology. Critical race theory enhances our understanding of variations in PCC. Minority oncology care is influenced by subtle PCC variations.